The moderating role of environmental-related innovation and technologies in growth-energy utilization nexus in highest-performing eco-innovation economies - Lasisi, Taiwo Temitop; Alola, Andrew Adewale; Muoneke, Obumneke Bob; Eluwole, Kayode Kolawole (Elsevier, 2022)
In pursuance of SDG 7, 8 and 12, unearthing the substantive role of environmental-related innovations and technologies in mitigating the undesirable effects of fossil fuel dependence and natural resources consumption on the environment in selected highest performing eco-innovation economies unveils cutting edge policy options to aspiring eco-innovation economies. Considering the selected panel of leading eco-innovation economies (Austria, Denmark, Finland, France, Germany, Netherland, Spain, and Sweden), this study examines the contribution of oil utilization, environmental-related technologies-innovations, and the moderating role of environmental-related technologies-innovations in energy-economic output nexus over the period 1990–2020. By employing the recently developed method of moments quantile regression approach alongside long-run estimator and Granger causality approaches as robustness, we found that oil utilization and environmental technologies spur economic growth in the countries while environmental innovations hinder output. Yet, environmental technologies further moderate the positive effect of oil utilization on economic prosperity but the disservice effect of environmental-related technological innovation is further exemplified when such innovation is applied to the oil consumption network. Moreover, while a one-way Granger causality evidence is established from environmental technologies to economic output, there is statistical evidence of a bi-directional causal relationship from oil utilization and environmental-related technological innovation to economic output. The policy relevance of this study further unearths the importance of the valuation of cost-effectiveness and energy efficiency of economic inputs such as technology-related inputs, especially during the design and manufacturing process.
Keywords: Co-innovation; Energy; Method of moments quantile regression; Panel investigation; Technological innovation; sustainable development; fi=Taloustiede|en=Economics|